Contemporary pedagogical approach in teaching Islamic education: navigating challenges and considerations - Ismail, Halim; Mohammad Shazwan, Nazifa Izzati (iConferences, 2024)
Through descriptive analysis, this study makes a unique contribution to Islamic education by delving into the contemporary challenges in the pedagogical approach, specifically, the dichotomy of modern vs. traditional methods and technology integration in teaching and learning. The findings of this study illuminate the pivotal role of the pedagogical approach in effective teaching and learning, particularly in the context of Islamic education. Balancing traditional and modern methods is a key challenge in implementing a pedagogical approach. As the new generation evolves, the traditional method can be effectively combined with modern approaches and technology to engage students and enhance their understanding of a topic. Technology integration in teaching Islamic education offers many benefits, including increased engagement, accessibility, and collaborative learning opportunities. This potential for increased engagement and accessibility through technology is exciting. It motivates Islamic Education Teachers to explore these possibilities, envisioning a future of Islamic education that is dynamic and interactive.